Strengthening Amazon conservation through community‐based voluntary patrolling - Caetano L. B. Franco; Thais Q. Morcatty; Helder L. Queiroz; Michael G. Sorice; Julia E. Fa; Paulo Roberto e Souza; Isabel S. Sousa; João Valsecchi; Hani R. El Bizri (Conservation Biology, 2025)
Globally, environmental crimes are a major threat to biodiversity and the livelihood of local populations. Community‐based protection of natural resources, which involves local people in surveillance and enforcement, is an important complement to the government‐led command‐and‐control policing approach. We examined whether a community‐based voluntary patrolling system deterred environmental crimes in Amazonia. We used data on environmental crimes recorded by patrollers over 11 years (2003–2013) in 12 independent territorial units in 2 large protected areas (PAs) in Amazonas, Brazil. For comparison, we also analyzed data from government‐led enforcement operations outside these PAs from 2002 to 2012. In total, patrollers conducted almost 20,000 surveillance outings (around 150,000 h of activity) and recorded the occurrence of 1260 crimes. Of the 772 crimes for which we had data on seized items, most violations were related to fishing (78.24%), 19.04% to hunting, or 2.72% to logging. The occurrence of crimes per outing increased as the number of patrollers and time spent patrolling increased and was greater during outings that were informant led. There was a sharp decrease over time in the occurrence of crimes during patrols across 11 of the 12 territorial units examined. Overall, the occurrence of crimes declined by approximately 80% over the study period. In contrast, the number of crimes detected over time during government‐led enforcement operations outside the PAs did not decline. Leadership of local communities in the planning and conducting of patrols contributed to rule conformity and enforcement in the PAs. Our results should be especially useful to managers of PAs and researchers in other parts of the tropics as a model for local patrolling and natural resource protection.

Aspergillosis in a colony of Humboldt penguins (Spheniscus humboldti) in a french zoological park: evaluation of environmental exposure - Tristan Bralet; Veronica Risco-Castillo; Isabel Valsecchi; Sylvie Laidebeure; Anaïs Sailler; Alexis Lécu; Françoise Botterel; Jacques Guillot; Pascal Arné; Grégory Jouvion (Veterinary Research Communications, 2024)